Assessment of precautionary measures against COVID-19 in Indonesian workplaces - Muhammad Ricky Pratama; Agung Supriyadi; Nurhalina Sari (International Journal of Public Health Science (IJPHS), 2021)
As the coronavirus disease 19 (COVID-19) pandemic spread across Indonesia, the precautionary measures have been taken by nearly all stakeholders, including industries and employers. The purpose of this study is to assess the measures took against COVID-19 pandemic in the workplaces across the country. This research involved participants from 103 different companies using a questionnaire adapted from Better Work Indonesia (BWI), occupational safety and health association (OSHA) and centers for disease control and prevention (CDC) COVID-19 guidelines. The data analysis conducted with descriptive statistics that resulted with the following key findings. Indonesian companies have taken precautionary measures against COVID-19 at their workplace. Most aspects of COVID-19 preventive measures: policy and procedure, operational aspect, health and safety, and external activities have been observed by the vast majority of the subjects. This study found that among 30 COVID-19 programs, the emergency exercise at work was the only one that had not been conducted by more than half of respondents. As the number of active cases still growing at the time this study conducted, all precautionary measures against COVID-19 shall be carried out with consistency by the company management).